Impact Of Disclosure Green Intellectual Capital, Green Innovation, And Corporate Social Responsibility On Firm Value With Financial Performance And Environmental Performance As Intervening Variables: A Study On Companies Food And Beverage On The Indonesian Stock Exchange - Fiyelex, Riandi; Hwihanus; R. Pandin, Maria Yovita R. Pandin (Indonesian Journal Economic Review (IJER), 2025)
The research method uses a quantitative approach with secondary data from annual reports and sustainability reports. The research population is companies in food and beverage listed on the IDX and PROPER for the 2021-2023 period. The research sample consisted of 9 companies with a total of 27 observations over three years. The data analysis technique used Structural Equation Modeling with Partial Least Square (PLS-SEM) version 2.0 M3 to test 18 research hypotheses. The results of the study showed that green intellectual capital does not have a significant effect on firm value, financial performance, and environmental performance. Green Innovation Significant effect on firm value, but no significant effect on financial performance and environmental performance. Corporate social responsibility has a significant effect on financial performance, environmental performance, and firm value. Financial performance has a significant effect on firm value, while environmental performance does not have a significant effect on financial performance and firm value. The results of the mediation test indicate that financial performance and environmental performance are not proven to be mediating variables in the relationship between independent variables and firm value. This study contributes to the literature on green business practices and corporate value in the context of the Indonesian food and beverage industry.